Amniotic Fluid Embolism - Darshandhari, Gayatri (Journal of Nursing Education of Nepal, 2023)
Amniotic fluid embolism (AFE) is a devastating obstetric complication that requires early and aggressive intervention with optimal cardiopulmonary resuscitation, as it has high morbidity and mortality. Immediate recognition and diagnosis of AFE is essential to improve maternal and fetal outcomes. The true incidence of this entity is unclear because this syndrome is difficult to identify and the diagnosis remains one of exclusion, with possible under-reporting of nonfatal cases. AFE is caused by abnormal activation of immunologic mechanisms following entry of fetal antigens into maternal circulation. AFE classically presents as a sudden cardiovascular collapse associated with respiratory compromise, fetal distress and development of a coagulopathy. Treatment of AFE is supportive and directed at treating cardiovascular, pulmonary, and coagulation derangements.